Fifty hikes in Maine : day hikes and backpacking trips, from the coast to Katahdin - Gibson, John, 1940- (Somersworth : New Hampshire Publishing Company, 1976)
Day Hikes and Backpacking Trips From the Coast to Katahdin
Keywords: Rock climbing -- Maine; Hiking -- Maine; Backpacking -- Maine; Trails -- Maine; Maine -- Description and travel -- 1951- -- Tours